Geo-portal for drought and climate risks in the region of Murcia: GOSYD project - Erena M.; García S.; Correal E.; Perez P.; Baños I.; Montesinos S.; García P.; Atenza J. (Drought management: scientific and technological innovations, 2008)
The management of climate risks, in particular drought management, requires handling a wide range of data, generally from different sources, sharing a common spatial component that makes it possible to map it. In this sense, and under the INSPIRE directive of the European Commission establishing an Infrastructure for Spatial Information in the European Community, different Spatial Data Infrastructures (SDI) are being developed at different levels. These SDIs can be accessed through Internet geo-portals, whose primary objective is to facilitate access to geographic data (geo-data) and related information. Under this approach, the GOSYD project is a first step to build an SDI for the region of Murcia capable of providing an integrated infrastructure for querying and managing data related to climate, drought and desertification risks. This SDI, based on the Web Map Services (WMS) developed by the Open Geospatial Consortium (OGC), will assist the technicians of the regional administration in their decision-making processes.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)